Menentukan Arah Kiblat dengan Metode Rashdul Kiblat - Khalid Shafaruddin; Rudi Piliang; Agus Sucipto (Jurnal Pelita Nusantara, 2025)
This research extensively examines alternative methods based on celestial mechanics and astronomy namely the Global Rashdul Qibla (Istiwa A'zam) and the Daily (Local) Rashdul Qibla methods as comprehensive solutions for achieving high-precision Qibla direction. Utilizing a qualitative research design with a mathematical approach using spherical trigonometry and simulated field observations, this study formulates standard operating procedures for Qibla calibration using solar shadow instruments, ranging from simple gnomons to the modern modified Mizwala Qibla Finder instrument. Simulations of spatial observation data at several coordinate points in Indonesia demonstrate that the solar shadow method can reduce deviation errors to less than five arcminutes (0° 5'), far surpassing the reliability of digital compasses, which consistently exhibit deviation distortions ranging from 1° to 5°. The conclusion of this study confirms that the Rashdul Qibla method definitively resolves the issue of Earth's magnetic anomalies. It is easily implemented communally by the public without requiring geodetic expertise or expensive optical instruments, and is highly recommended as the primary standard for calibrating the orientation of places of worship, with the operational caveat that it relies on clear meteorological weather conditions.